The Occupational Status of Jews in the United States on the Eve of the US Civil War - Barry R. Chiswick (Institute of Labor Economics (IZA), 2018)
The Public Use Microdata Sample (PUMS) from the 1860 Census of Population (one percent sample of free people) is used to study the occupational distribution and the determinants of socio-economic status of Jewish men (age 16 to 60) compared to other free men. Jews cannot be identified directly, but two versions of the Distinctive Jewish Name (DJN) technique are used to identify men with a higher probability of being Jewish. The men identified as likely to be Jewish are more likely to be in managerial, clerical, machine operator, and sales (especially as peddlers) occupations. They are less likely to be in farm related occupations as owners, tenants, managers, or laborers. Using multiple regression analysis to study the Duncan Socio-Economic Index (SEI), it is found that the index increases with age (at a decreasing rate), literacy, being married, and living in the South. It is lower among (free) non-whites, among the foreign-born, those with more children, and those living in rural areas (especially on farms). Other variables the same, US-born Jews do not differ significantly in SEI from other free, native-born men, but foreign-born Jews have a significantly higher SEI than other immigrants or even US-born non-Jews.
Keywords: N31; J62; J15; 330; 1860 US Census; occupational status; Jews; foreign born; labor history